On the determination and macroeconomic consequences of public financial policy - Kremers, J; Kremers, Jeroen J. M. (1986)
﻿ This study develops a theoretical framework for the analysis of regular patterns in public financial behaviour, and applies that framework in an empirical assessment of budgetary policies in the United States and in the Netherlands. Its purpose and scope are threefold. First, it sheds theoretical light on economic considerations guiding public financial behaviour in a dynamic model of optimal taxation. The resulting idea, that it may be sensible to smooth taxation over time,is subsequently extended to a more general model of the public finances, which involves spending, taxation, debt and money creation in an effort to control the government budget. Second, using modern econometric methods the practical relevance of this model is illustrated with estimations for the United States and the Netherlands. Third, the model is sufficiently flexible to allow for a number of more institutional insights. In this respect the emphasis is placed on the Dutch economy and public finances. The thesis thus engages economic theory, econometric technique and institutional and macroeconomic background in a combined effort to understand and evaluate regular patterns in public financial behaviour. Its findings have implications for each of these three areas of economic interest.